The Effect of Date Palm Pollen Capsule on orgasm and sexual satisfaction in Menopausal Women: A double-blind controlled clinical trial - Sedigheh Yosefzadeh; Somayeh Sadeghi; Hassan Rakhshandeh; Salameh Dadghar; Seyed Reza Mazloum (Mashhad University of Medical Sciences, 2017)
Introduction: Decreased sexual satisfaction and lack of orgasm in sexual relations are of the most common problems in postmenopausal women that affect their quality of life. In traditional medicine books, pate palm pollen is introduced as sexual enhancer plant and in recent researches, it has improved sexual behavior in animals, but no study which examines date palm pollen on sexual function in humans has not been conducted; therefore this study was performed with aim to evaluate the effect of date palm pollen capsules on sexual satisfaction and orgasm in menopausal women. Methods: This double-blind clinical trial with placebo group was performed on 60 ‌menopausal women with natural menopause and without any sexual function disorder who referred to health centers of Mashhad in 2016. Participants were randomly assigned to two groups: receiving date palm pollen and placebo for 35 days. The research tool was female sexual function Index (FSFI) that a part of which assessed sexual satisfaction and orgasm. The sexual function of women was evaluated before and after treatment. Data were analyzed by SPSS software (version 16) and Fisher-Exact, Mann-Whitney, Paired-t, and independent-t tests. P < 0.05 was considered significant. Results: The mean change in orgasm score of ‌menopausal women after the intervention was significantly higher in the intervention group than the control group (P= 0.004). The mean change in sexual satisfaction score after the intervention was not significant in the intervention and control group (P=0.122). Conclusion: The use of date palm pollen improves orgasm in menopausal women, but has no effect on their sexual satisfaction.